Effects of Global Payment and Accountable Care on Medication Treatment for Alcohol and Opioid Use Disorders. Issue 1 (January 2018) - Donohue, Julie M.; Barry, Colleen L.; Stuart, Elizabeth A.; Greenfield, Shelly F.; Song, Zirui; Chernew, Michael E.; Huskamp, Haiden A.
Abstract : Objectives: The Alternative Quality Contract (AQC) implemented in 2009 by Blue Cross Blue Shield of Massachusetts (BCBSMA) is intended to improve quality and control costs by putting providers at risk for total medical spending and tying payment to performance on specified quality measures. We examined the AQC's early effects on use of and spending on medication treatment (MT) for addiction among individuals with alcohol use disorders (AUDs) and opioid use disorders (OUDs), conditions not subject to any performance measurement in the AQC. Methods: Using data from 2006 to 2011, we use difference-in-difference estimation of the effect of the AQC on MT using a comparison group of enrollees in BCBSMA whose providers did not participate in the AQC. We compared AQC and non-AQC enrollees with AUDs (n = 37, 113 person-years) and/or OUDs (n = 12, 727 person-years) on any use of MT, number of prescriptions filled, and MT spending adjusting for demographic and health status characteristics. Results: There was no difference in MT use among AQC enrollees with OUD (38.7%) relative to the comparison group (39.1%) (adjusted difference = −0.4%, 95% confidence interval −3.8% to 3.0%, P  = 0.82). Likewise, there was no difference in MT use for AUD between the AQC (6.3%) and comparison group (6.5%) ( P  = 0.64). Similarly, we detected no differences in number of prescriptions or spending. Conclusions: Despite incentives for improved integration and quality of care under a global payment contract, the initial 3 years of the AQC showed no impact on MT use for AUD or OUD among privately insured enrollees with behavioral health benefits. Abstract : Supplemental Digital Content is available in the text